2017
DOI: 10.1074/jbc.m116.769430
|View full text |Cite
|
Sign up to set email alerts
|

The Proprotein Convertase Subtilisin/Kexin Type 9-resistant R410S Low Density Lipoprotein Receptor Mutation

Abstract: Edited by George M. CarmanFamilial hypercholesterolemia (FH) is characterized by severely elevated low density lipoprotein (LDL) cholesterol. Herein, we identified an FH patient presenting novel compound heterozygote mutations R410S and G592E of the LDL receptor (LDLR). The patient responded modestly to maximum rosuvastatin plus ezetimibe therapy, even in combination with a PCSK9 monoclonal antibody injection. Using cell biology and molecular dynamics simulations, we aimed to define the underlying mechanism(s)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 72 publications
(79 reference statements)
1
32
0
Order By: Relevance
“…Accordingly, in IHH cells only the H449R mutation led to a significant GOF on the LDLR, but not H449L or H449A (Fig. C), reinforcing the notion that the parameters regulating the activity of PCSK9 are different in both pathways , and that a positive charge at residue 449 (e.g., Arg) enhances the intracellular activity of PCSK9, but not its extracellular one.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…Accordingly, in IHH cells only the H449R mutation led to a significant GOF on the LDLR, but not H449L or H449A (Fig. C), reinforcing the notion that the parameters regulating the activity of PCSK9 are different in both pathways , and that a positive charge at residue 449 (e.g., Arg) enhances the intracellular activity of PCSK9, but not its extracellular one.…”
Section: Resultssupporting
confidence: 68%
“…C). Immunocytochemical analysis of these cells under nonpermeabilizing conditions allowed us to assess the levels of the LDLR at the cell surface (green) and DiI‐LDL uptake (red) probed the LDLR functional activity . The data revealed that all natural mutants of PCSK9, including H449L, represent significant LOF mutations as clearly evident by increases in both LDLR levels and DiI‐LDL internalization compared to WT (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations